Cardiac arrhythmias in Dravet syndrome: an observational multicenter study. Issue 4 (24th March 2020) - Shmuely, Sharon; Surges, Rainer; Helling, Robert M.; Gunning, W. Boudewijn; Brilstra, Eva H.; Verhoeven, Judith S.; Cross, J. Helen; Sisodiya, Sanjay M.; Tan, Hanno L.; Sander, Josemir W.; Thijs, Roland D.
Abstract: Objectives: We ascertained the prevalence of ictal arrhythmias to explain the high rate of sudden unexpected death in epilepsy (SUDEP) in Dravet syndrome (DS). Methods: We selected cases with clinical DS, ≥6 years, SCN1A mutation, and ≥1 seizure/week. Home‐based ECG recordings were performed for 20 days continuously. Cases were matched for age and sex to two epilepsy controls with no DS and ≥1 major motor seizure during video‐EEG. We determined the prevalence of peri‐ictal asystole, bradycardia, QTc changes, and effects of convulsive seizures (CS) on heart rate, heart rate variability (HRV), and PR/QRS. Generalized estimating equations were used to account for multiple seizures within subjects, seizure type, and sleep/wakefulness. Results: We included 59 cases. Ictal recordings were obtained in 45 cases and compared to 90 controls. We analyzed 547 seizures in DS (300 CS) and 169 in controls (120 CS). No asystole occurred. Postictal bradycardia was more common in controls ( n  = 11, 6.5%) than cases ( n  = 4, 0.7%; P  = 0.002). Peri‐ictal QTc‐lengthening (≥60ms) occurred more frequently in DS ( n  = 64, 12%) than controls ( n  = 8, 4.7%, P  = 0.048); pathologically prolonged QTc was rare (once in each group). In DS, interictal HRV was lower compared to controls (RMSSD P  = 0.029); peri‐ictal values did not differ between the groups. Prolonged QRS/PR was rare and more common in controls (QRS: one vs. none; PR: three vs. one). Interpretation: We did not identify major arrhythmias in DS which can directly explain high SUDEP rates. Peri‐ictal QTc‐lengthening was, however, more common in DS. This may reflect unstable repolarization and an increased propensity for arrhythmias.